2019
DOI: 10.1002/jcla.22928
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic performance of light‐initiated chemiluminescent assay compared with the Architect chemiluminescence immunoassay for detection of HCV antibody

Abstract: BackgroundHepatitis C virus antibody (anti‐HCV) test had been approved as a preliminary screening test for HCV infection. Light‐initiated chemiluminescent assay (LiCA) was a homogenous method. We aimed to assess the clinical diagnostic performance of LiCA and compare it with that of chemiluminescence immunoassay (CLIA) which was widely used in clinical laboratories.MethodsA total of 10 772 patients from the Peking University Third Hospital were enrolled. The serum samples were detected on the ChIVD LiCA500 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This may partly explain why the quantitative HBsAg results in our studies are genotype independent. Previous data have shown that LICA-like technology is suitable for detecting small molecules such as hormones and some new drugs, and for detecting antibodies against pathogens (25,(41)(42)(43)(44). Our study shows that the LICA technology could also be extended to the measurement of much larger analytes, such as HBsAg, which is composed of various forms of particles with diameters ranging from 17 to 45 nm (8,45).…”
Section: Discussionmentioning
confidence: 68%
“…This may partly explain why the quantitative HBsAg results in our studies are genotype independent. Previous data have shown that LICA-like technology is suitable for detecting small molecules such as hormones and some new drugs, and for detecting antibodies against pathogens (25,(41)(42)(43)(44). Our study shows that the LICA technology could also be extended to the measurement of much larger analytes, such as HBsAg, which is composed of various forms of particles with diameters ranging from 17 to 45 nm (8,45).…”
Section: Discussionmentioning
confidence: 68%
“…[6][7][8] Various assays based on this technology have been developed recently. [14][15][16] In this study, we have validated the analytical and diagnostic performance of the LiCA thyroid assays.…”
Section: Discussionmentioning
confidence: 96%
“…Though with high sensitivity and accuracy, it also has certain disadvantages. For example, the above immunoassay requires several washing steps as well as solid-phase immobilization of antibodies, which is time-consuming and laborious (13). Similarly, liquid chromatography-tandem mass spectrometry (LC-MS/ MS) is also an emerging technology for the detection of small molecular hormones (14,15), but its high cost and low degree of automation limit its popularity and application in clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%